Community Participation in the Development of the Petai River Tourism Village, Kampar District - Riau Nurita; Firdaus Yusrizal; Ahmad Nawawi; Fahmi Muhammad; Nurarini Yulia (Global Writing Academica Researching and Publishing, 2026)
The development of community-based tourism villages is one of the strategies for sustainable tourism development in Indonesia. The success of tourism village development is largely determined by the level of participation of local communities as the main actors. This study aims to analyze the forms of community participation, supporting and inhibiting factors of participation, and their implications for the development of Sungai Petai Tourism Village, Kampar District. The study uses an interpretive paradigm with a descriptive qualitative approach within the Community Based Tourism (CBT) framework. Data collection techniques include in-depth interviews, field observations, and documentation studies. Research informants were determined purposively, including village officials, tourism village managers, community leaders, youth, and local business actors. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that community participation has occurred but is still dominated by the implementation stage of activities, while involvement in planning and decision-making is still limited. Supporting factors for participation include the natural potential of Sungai Petai and the community's spirit of mutual cooperation, while inhibiting factors include limited human resource capacity, low access to information, and non-inclusive tourism village management institutions. This study recommends developing a more inclusive model of community participation through strengthening village tourism institutions, particularly by examining in-depth the mechanisms of community involvement in the planning and decision-making stages to achieve sustainable village tourism development.